2011
DOI: 10.1016/j.tvjl.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Length asymmetry of the bovine digits

Abstract: The lengths of the digital bones of the fore-and hind-limbs obtained post mortem from 40 cattle of different ages were measured using digital radiographs. The lengths of the individual digital bones and the overall length of the digit were determined using computer software. The lateral metacarpal/metatarsal condyle, and lateral P1 and P2 were significantly longer than their medial counterparts, whereas P3 of the medial digit was longer than its lateral partner. Measured from the cannon bone epiphysis to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
7
45
2
9
Order By: Relevance
“…The bone lengths established in the present study were close to the lengths observed in different breeds of bovine, by direct measurements (Ocal et al, 2004;Nacambo et al, 2007;Radisic et al, 2012) and radiographic measurements (Schwarzmann et al, 2007;Muggli et al, 2011). As well as, in buffalo bones (Nourinezhad et al, 2012) and in wild animal radiographies (Keller et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The bone lengths established in the present study were close to the lengths observed in different breeds of bovine, by direct measurements (Ocal et al, 2004;Nacambo et al, 2007;Radisic et al, 2012) and radiographic measurements (Schwarzmann et al, 2007;Muggli et al, 2011). As well as, in buffalo bones (Nourinezhad et al, 2012) and in wild animal radiographies (Keller et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…The Curraleira and Pantaneira measurements were similar to the measurements in Holstein male cattle (Ocal et al, 2004). The lengths of the Nellore bones were similar as those described by Muggli et al (2011) in heifers and steers of different breeds. For buffaloes, the mean values in our study were distinctively greater than the values of the Table 2.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A ocorrência de pododermatite infecciosa está relacionada com pisos irregulares das instalações e tratamentos inadequados realizados por práticos despreparados (Romani et al, 2004). Estes autores mostraram também que a pododermatite infecciosa atinge com maior frequência os membros pélvicos e no trabalho de Molina et al (1999) mostrou-se que 66% das enfermidades digitais ocorreram nestes membros e esta se deve as diferenças anatômicas entre os dígitos dos membros pélvico e torácicos e entre os dígitos de cada membro (Muggli et al, 2011). Neste contexto, percebe-se que o conhecimento da biomecânica das diversas estruturas que compõem os dígitos é fundamental para o controle dos fatores determinantes e predisponentes que envolvam podopatias e claudicações dos bovinos leiteiros.…”
Section: Anatomia Dos Dígitos Nutrição Instalações E Ambiente No Counclassified